Implementation and Effectiveness of the Monday.com Digital Application in the Improvement Achievements Program of Occupational Health and Sports at Singaparna Public Health Center, Tasikmalaya District - Cecep Heriana; Imam Subekkti, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Digital health transformation represented a significant shift in how health services were delivered, managed, and accessed through digital technology. Implementing digital management tools was essential for overseeing health programs in primary healthcare settings. This study aimed to evaluate the effectiveness of the Monday.com application in enhancing the outcomes of occupational health and sports programs at the Singaparna Community Health Centre. Method: A qualitative study with an action research approach was employed to assess the Monday.com application, which was implemented for managing occupational health and sports programs targeted at program managers at the Singaparna Community Health Centre. The primary measure used was the timeliness of program implementation against established targets. The research themes were input, process, and output. The stages of this research included identification, implementation, and evaluation of the effectiveness program. Data were collected through interviews and observations, utilizing the digital application Monday.com and a questionnaire. Data analysis involved a qualitative study with content analysis using the screenQ application. Results: The results of the digital transformation indicated an increase in program achievements. Specifically, two programs were completed, and four additional programs were in the implementation stage. The program could be managed effectively with notifications sent 3 days in advance via email or phone, allowing the program manager to implement the plan accordingly. Conclusion: The use of the Monday.com application proved effective in increasing the coverage and impact of the occupational health and sports programs at the Singaparna Health Centre. Recommendation: Community health canters were encouraged to adopt the Monday.com application to enhance the monitoring and implementation of their health programs.